Hybrid Energy System - Optimization and New Concept - Morávek, Jan; Mastný, Petr (Lublin University of Technology, 2014)
Paper presents a research related to the design of a new concept of hybrid energy system. It describes actually used concepts and the benefits of new design. Subsequently, the problems of the proper systems setting and working conditions are discussed and the new concept of the systems settings is presented. Research is further enhanced by comparing with the simulation model assuming the weather data acquired for the test location. The measured data are compared with the results of simulation.

Paper presents a research related to the design of a new concept of hybrid energy system. It describes actually used concepts and the benefits of new design. Subsequently, the problems of the proper systems setting and working conditions are discussed and the new concept of the systems settings is presented. Research is further enhanced by comparing with the simulation model assuming the weather data acquired for the test location. The measured data are compared with the results of simulation.
Hybrid Energy System - Optimization and New Concept
Keywords: Hybrid energy system; MATLAB simulation; optimization; Hybrid energy system; MATLAB simulation; optimization